Common single nucleotide polymorphisms at the NPC1L1 gene locus significantly predict cardiovascular risk in coronary patients. Issue 1 (September 2015) - Muendlein, Axel; Leiherer, Andreas; Saely, Christoph H.; Rein, Philipp; Zanolin, Daniela; Kinz, Elena; Brandtner, Eva-Maria; Fraunberger, Peter; Drexel, Heinz
Abstract Background Niemann-Pick C1-like 1 (NPC1L1) is involved in dietary cholesterol absorption and is the direct molecular target of the LDL-lowering drug ezetimibe. Recently, genetic variants in NPC1L1 have been associated with the incidence of cardiovascular events, but it remains unclear if the impact of NPC1L1 on cardiovascular risk is dependent on its role in cholesterol absorption. Furthermore, no direct association of genetic variants in NPC1L1 with coronary atherosclerosis has been established. Methods To further address these issues, we determined the impact of 34 single nucleotide polymorphisms (SNPs) at the NPC1L1 gene locus on the presence of coronary atherosclerosis and prospectively on future cardiovascular events in a cohort of 984 angiographied Caucasian patients. Results Out of investigated SNPs, 24 variants were significantly associated with future cardiovascular events. The highest impact was observed for rs55837134 (sex-and age adjusted additive HR = 1.67 [1.28–2.18]; p = 1.3 e-4). Regression analysis conditioned on rs55837134 showed that significant associations between remaining SNPs at the NPC1L1 locus and vascular events did not persist suggesting their dependence on rs55837134. Its significant association remained almost unchanged after further adjustment for total cholesterol, LDL cholesterol, and other cardiovascular risk factors (additive HR = 1.67 [1.28–2.18]; p = 1.7 e-4). In addition, no significant association of investigated NPC1L1 variants with coronary atherosclerosis could be observed, at least after false discovery rate correction. Conclusions Genetic variants of NPC1L1, particularly rs55837134, show a predictive impact on cardiovascular events. Further studies to determine the molecular consequences of common genetic variants in NPC1L1 are needed.